2018
DOI: 10.24095/hpcdp.38.2.01
|View full text |Cite
|
Sign up to set email alerts
|

Youth self-report of child maltreatment in representative surveys: a systematic review

Abstract: Introduction This systematic review identified population-representative youth surveys containing questions on self-reported child maltreatment. Data quality and ethical issues pertinent to maltreatment data collection were also examined. Methods A search was conducted of relevant online databases for articles published from January 2000 through March 2016 reporting on population-representative data measuring child maltreatment. Inclusion criteria were established a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 96 publications
1
27
0
Order By: Relevance
“…A recent review suggests that youth self-report surveys conducted with careful attention to ethics and confidentiality are a viable way of collecting information on the occurrence of child maltreatment incidents. 34 Such surveys would be useful in assessing the need for support services to children and families, and for programs aimed at eradicating CSA.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review suggests that youth self-report surveys conducted with careful attention to ethics and confidentiality are a viable way of collecting information on the occurrence of child maltreatment incidents. 34 Such surveys would be useful in assessing the need for support services to children and families, and for programs aimed at eradicating CSA.…”
Section: Discussionmentioning
confidence: 99%
“…In order to enhance data accuracy when investigating child maltreatment through a population survey, the present study applies a variety of strategies discussed in previous methodological reviews in this field of research. 14 36 In addition to asking various behaviour-specific questions about specific forms of abuse, it also included items about developmental timing of the exposure. This makes it possible to investigate both characteristics of the type of abuse and also how developmental timing relates to various outcomes.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…This may in turn reduce the influence of recall bias. 14 Furthermore, it is suggested that adolescents' self-report is more reliable compared with children under the age of 10 years. 15 In addition, identifying this population at an early stage in their life has several important benefits, given the potentially detrimental consequences that both mental and physical health problems have on subsequent educational, social and economic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The YSR/11-18 (Achenbach, 1991b) has been widely used in clinical practice and in psychopathological research due to its usefulness in establishing a quantitative taxonomy. In the last decade, this measurement was used in different populations in order to explore distinct objectives such as investigate which YSR/11-18 items or scales can be used best to predict anxiety disorders in adolescents (Ferdinand, 2007), determine its contribution in the diagnosis of psychiatric comorbidity of juvenile primary headache disorders (Toros et al, 2010), examine emotional and behavioral problems among school adolescents with and without reading difficulties as measured by the YSR/11-18 (Undheim, Wichstrom, & Sund, 2011), test the measurement invariance of the attention and thought problems subscales in a population-based sample of adolescents with and without epilepsy (Ferro, Boyle, Scott, & Dingle, 2014), examine the relationship between weight and psychological distress in Hispanic with excess weight (Yates et al, 2014), detect mental health problems in children's and adolescents in residential care (Sainero, del Valle, & Bravo, 2015), examine the prevalence and characteristics of the dysregulation profile of adolescents based on data from the YSR/11-18 (Jordan, Rescorla, Althoff, & Achenbach, 2016), investigate to what extent emotional and behavioral problems impact on and explain the academic performance of adolescents (Rosso, & Helena, 2017), and identified population-representative youth surveys containing questions on self-reported child maltreatment (Laurin, Wallace, Draca, Aterman, & Tonmyr, 2018).…”
Section: Modifications and Several Uses Of The Ysr/11-18mentioning
confidence: 99%